2021
DOI: 10.3389/fmicb.2021.714993
|View full text |Cite
|
Sign up to set email alerts
|

Compartment Niche Shapes the Assembly and Network of Cannabis sativa-Associated Microbiome

Abstract: Interactions between plants and microbes may promote the growth of plants and regulate the production of secondary metabolites. Hemp (Cannabis sativa) is an annual herb and an important commercial crop. However, the assembly and network of hemp-associated microbiomes inhabiting in soil and plant compartments have not been comprehensively understood. This work investigated the assembly and network of bacterial and fungal communities living in soils (bulk and rhizosphere) and plant compartments (root, stem, leaf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 70 publications
(73 reference statements)
2
26
1
Order By: Relevance
“…At genus resolution, plant samples showed a high abundance of genera that have been already described as endophytes: Exophiala (Yu et al, 2021), Monosporascus (Guo and Zou, 2020), Paraphoma (Kang et al, 2021), Plectospherella (Feng et al, 2021;Wei et al, 2021), Podospora (Penner and Sapir, 2021). Some of these genera were even identified in Brassicaceae plant endospheres, including Exophiala (Maciá-Vicente et al, 2016), Plectosphaerella (Plaszkó et al, 2020;Ważny et al, 2021), Setophoma (Szűcs et al, 2018;Poveda et al, 2020), or as a common pathogen: Thanatephorus (teleomorph of Rhizoctonia) (Dean et al, 2012).…”
Section: Fungal Community Composition and Diversitymentioning
confidence: 99%
“…At genus resolution, plant samples showed a high abundance of genera that have been already described as endophytes: Exophiala (Yu et al, 2021), Monosporascus (Guo and Zou, 2020), Paraphoma (Kang et al, 2021), Plectospherella (Feng et al, 2021;Wei et al, 2021), Podospora (Penner and Sapir, 2021). Some of these genera were even identified in Brassicaceae plant endospheres, including Exophiala (Maciá-Vicente et al, 2016), Plectosphaerella (Plaszkó et al, 2020;Ważny et al, 2021), Setophoma (Szűcs et al, 2018;Poveda et al, 2020), or as a common pathogen: Thanatephorus (teleomorph of Rhizoctonia) (Dean et al, 2012).…”
Section: Fungal Community Composition and Diversitymentioning
confidence: 99%
“…For example, microbial communities are essential to maintaining soil homeostasis and to improving host productivity via the production of secondary metabolites ( 4 , 5 ), the suppression of pathogens ( 6 , 7 ), and the promotion of plant growth ( 8 ). However, different compartments provide various ecological niches, which are inhabited by highly distinct microbial communities ( 9 ), though the microbial diversity, community compositions, and assemblies among different compartment niches are still less documented. In order to improve our ability to predict the responses of ecosystem functions ( 10 ), it is crucial to seek a better understanding of the relationships between plants and microbes.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Fusarium , Ilyonectria , Cladosporium and Aspergillus were observed to have a distinctive abundance in the rhizosphere and phyllosphere of Vaccinium macrocarpon ( 25 ). Fungal Clitopilus and Mortierella were significantly enriched in the soil and root endosphere samples of the Cannabis sativa plant species compared with those of the aerial parts ( 9 ), and Phyllosticta vaccinii and P. elongata were frequently isolated from the developing ovaries of cranberry ( 26 ). All of these studies indicate that niche differentiation can result in compositional and structural variations in microbial communities across different plant-related compartments.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is speculated that Chinese chives contain endophytic bacteria or associate with rhizospheric microorganisms that can inhibit pathogens. In the microbial analysis of various ecological compartments of other plants, it can be found that ecological compartments have effects on microbial composition and microbial community function (Wei et al, 2021 ). However, the current studies on plant ecological compartments are mostly between underground compartments (especially in the rhizosphere and root surface), and the composition differences of soil microorganisms, rhizosphere microorganisms, and root endosphere microorganisms and the screening mechanism of roots are studied (Reinhold Hurek et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%